Stress and resilience and associated factors among nursing undergraduates in the early stages of the COVID-19 pandemic - Shainulabdeen Fathima Nasath; Ilankoon Mudiyanselage Prasanthi Sumudri Ilankoon (Intelektual Pustaka Media Utama, 2022)
Personal, academic and clinical factors are the main stressors for nursing undergraduates. This study aimed to assess stress, resilience and associated factors among nursing undergraduates. A descriptive cross-sectional study was conducted among nursing undergraduates at one university in Sri Lanka. A self-administered questionnaire including demographics, Perceived Stress Scale and Resilience Scale for Adults was used. Data were analyzed using independent sample t-test, ONE WAY ANOVA and binary logistic regression model. This study found that 38% of undergraduates had a high level of stress and the majority had a moderate level of resilience (76.7%). The mean total resilience score (RS) was 102.4 (±5.53). “Not getting expected marks” adjusted odds ratio (AOR) 5.56, 95 % CI=1.37-22.6) and “not satisfied with the academic program” (AOR 4.87, 95 % CI=1.27-8.76) were found to be the factors for having a high-stress score. Statistically significant median RS differences were observed: “Perception of Self” with grade point average (p=0.02) and recreational activities (p=0.04), and “Perception of future” with gender (p=0.04), the physical well-being (p=0.03) and recreational activities (p=0.04) and “Structural style” with the academic year (p=0.03). Influencing factors on stress and resilience need to be taken into account for organising academic programs for nursing undergraduates.